(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article reflects on the use of didactic games, plot games, role-playing games, business games, dramatic games and innovative forms of education with an innovative character in order to strengthen the educational and cognitive activity of students in modern conditions, improve the quality and effectiveness of training